Performance of ultra high performance concrete by using palm oil clinker as partially aggregate replacement - Noorhalilie, Ahmad Rosli (2019)
Construction industry has been growth from day to day. The requirement of concrete in this field has been increasing and the development in concrete industry has been improve when there is a new type of concrete which is high performance concrete and ultra-high performance concrete. Ultra-high performance concrete (UHPC) is a one of concrete type that has outstanding mechanical properties and a good durability as compared to normal concrete. However, this type of concrete has some limitation in terms of production cost and availability of raw materials. The production of UHPC, require the large amount of cement, sand and coarse aggregate. The use of palm oil clinker as partial aggregate replacement can reduce the problem arising due to the production of UHPC. The use of palm oil clinker in this study was stimulated from the environmental problem issue arising due to the disposal of palm oil industry waste and the production of natural aggregate. In this present study, the mechanical properties of UHPC incorporating with palm oil clinker (POC) as partially replacement of aggregate was investigate. Four (4) different percentage level of POC as partial replacement of coarse aggregate was prepared. 0%, 5%, 10%, and 15% of POC from the total of coarse aggregate were used. The specimens was label as plain UHPC with 0% of POC replacement, while for the concrete contain 5%, 10% and 15% POC replacement were label as POC-UHPC5, POC-UHPC10 and POC-UHPC15. Slump test was conduct on fresh concrete while compressive strength test and flexural strength test for hardened concrete. Slump test was conduct immediately after the mix and compressive strength test and flexural strength was tested after 7, 28 and 60 days of curing in water tank. The experimental result shows the reduction of compressive strength and flexural strength of UHPC contains POC as aggregate replacement specimens. It was revealed the increasing percentage of POC lead to decreasing the compressive strength and flexural strength of the specimens. Overall, the use of 10% POC as partial aggregate replacement show similar result on both compressive strength and flexural strength of the concrete.